Phytotoxicity of aluminum ions - O. V. Yakovleva (Труды по прикладной ботанике, генетике и селекции)
Russia contains the largest areas of soil with excessive acidity in the world. According to the results of agrochemical surveys of arable lands, the area of acidic soils (pH less than 5.5) is currently about 65 million hectares. The losses in agricultural products calculated in grain per year amount to 15-20 million tons. The negative effect of acid soil on plants is explained by the low content of exchangeable bases and the presence of large quantities of mobile forms of aluminum (2-20% from the weight of the soil). Absorption and assimilation of aluminum by plants depends on the forms by which it is represented in acidic soils. The importance of aluminum in plant life is ambiguous, as the reports on the toxic effect of aluminum ions are more numerous. High concentrations of aluminum directly or indirectly affect the processes of vital activity of plants: water regime, nitrogen metabolism, mineral nutrition, photosynthesis, oxidation-reduction reactions. Phytotoxic metal ions also affect various physiological and biochemical processes in plants, stimulate numerous anatomical and morphological changes. Excess aluminum ions in soil disrupt the mineral nutrition of plants. Various agrochemical methods are used to reduce the harmful toxic effect of aluminum ions on plants. Most plants are sensitive to high concentrations of aluminum. The resistance to toxic concentrations of metal ions in plants is due to the action of several mechanisms that are characteristic of each species. Some species of plants have protective mechanisms by which the adverse effects of toxic ions are reduced or completely eliminated. It has been established that root growth is the better indicator of resistance than the growth of the above-ground plant parts. The methods of diagnosing sensitivity to aluminum in the early stages of plant development are based on the change in root length after exposure to a stress factor. Knowledge of the genetic and physiological foundations of plant resistance to high concentrations of ions of heavy metals and aluminum is necessary for the search for tolerant genotypes of cultivated plants.